Why DeFi lending? Evidence from Aave V2 - Cornelli, Giulio; Gambacorta, Leonardo; Garratt, Rodney; Reghezza, Alessio (Journal of Financial Intermediation, 2025)
Decentralised finance (DeFi) lending protocols have experienced significant growth recently, yet the motivations driving investors remain largely unexplored. We use granular, transaction-level data from Aave, a leading player in the DeFi lending market, to study these motivations. Our theoretical and empirical findings reveal that the search for yield predominantly drives liquidity provision in DeFi lending pools, whereas borrowing activity is mainly influenced by speculative and, to some extent, governance motives. Both retail and large investors seek potential high returns through market movements and price speculation, however the latter engage in DeFi borrowing relatively more than the former also to influence protocol decisions and accrue more significant governance rights.